Serological profiles in the connective tissue diseases in Zimbabwean patients. Issue 1 (January 1989) - Davis, P; Stein, M; Ley, H; Johnston, C
Abstract : The serological profiles of 104 Zimbabwean patients with clinically diagnosed connective tissue diseases were determined. The prevalence of rheumatoid factor was less than would have been expected in other geographical groups, but the prevalence of antinuclear antibodies was similar. Despite considerable racial, socioeconomic, and genetic differences in our patient group compared with other previously published studies the specificity and sensitivity of antinuclear antibodies, notably to DNA and Sm, correlated well with clinical diagnoses. This study validates the use of these serological tests in the investigation of this group of patients.